2006
DOI: 10.1002/j.1551-8833.2006.tb07595.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale studies of Hexavalent Chromium Removal from drinking water

Abstract: The goal of this research was the initial evaluation of several pilot‐scale treatment technologies for hexavalent chromium removal to <5 μg/L (i.e., 95% removal). A major focus was to assess manufacturer‐provided pilot systems with media that were effective in bench‐scale studies as well as technologies that were promising but could not be appropriately tested at bench scale. The technologies tested included ion exchange systems (i.e., column strong‐base and weak‐base anion exchange and reactor‐based strong‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 11 publications
3
45
1
Order By: Relevance
“…This reduction is the first step in many effective water treatment strategies that is followed by conversion of the soluble Cr(III) to particulate Cr(OH) 3 or sorbed solids that can be settled or filtered from the water. The most common reductant is Fe(II), with reaction times on the order of seconds to hours, depending on pH (Blute, 2010; McGuire et al, 2006; Qin et al, 2005; Lee & Hering, 2003; Schlautman & Han, 2001; Buerge & Hug, 1999; El‐Shoubary et al, 1998; Pettine et al, 1998b; Buerge & Hug, 1997; Sedlak & Chan, 1997; Fendorf & Li, 1996; Henderson, 1994; Lin et al, 1992; Eary & Rai, 1988; Philipot et al, 1984). The presence of dissolved oxygen does not significantly interfere with reduction of Cr(VI) by Fe(II) (Schlautman & Han, 2001; Eary & Rai, 1988).…”
Section: General Reactions Of Cr(iii) and Cr(vi) In Water Treatment Amentioning
confidence: 99%
See 3 more Smart Citations
“…This reduction is the first step in many effective water treatment strategies that is followed by conversion of the soluble Cr(III) to particulate Cr(OH) 3 or sorbed solids that can be settled or filtered from the water. The most common reductant is Fe(II), with reaction times on the order of seconds to hours, depending on pH (Blute, 2010; McGuire et al, 2006; Qin et al, 2005; Lee & Hering, 2003; Schlautman & Han, 2001; Buerge & Hug, 1999; El‐Shoubary et al, 1998; Pettine et al, 1998b; Buerge & Hug, 1997; Sedlak & Chan, 1997; Fendorf & Li, 1996; Henderson, 1994; Lin et al, 1992; Eary & Rai, 1988; Philipot et al, 1984). The presence of dissolved oxygen does not significantly interfere with reduction of Cr(VI) by Fe(II) (Schlautman & Han, 2001; Eary & Rai, 1988).…”
Section: General Reactions Of Cr(iii) and Cr(vi) In Water Treatment Amentioning
confidence: 99%
“…A comprehensive review of Cr(VI) removal via engineered treatment processes was recently conducted (Sharma et al, 2008), and some comprehensive evaluations of viable treatment processes and cost evaluations have also been completed for Cr(VI) removal at California utilites (Blute & Wu, 2012; Blute et al, 2010; Blute, 2010; McGuire, 2010; McGuire et al, 2007, 2006; Qin et al, 2005; Lee & Hering, 2003; Drago, 2001). These have confirmed that treatment via reductive coagulation can easily obtain very low levels (< 5 µg/L) of Cr(VI) in water leaving the treatment plant.…”
Section: Engineering Considerations For Cr Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Cr(VI) pollution can increase the risk of catching dermatitis, rhinitis, and even cancer. 6 Many methods, such as physicochemical adsorption, 7 bioremediation, 6 chemical reduction, 8 precipitation, 9 membrane separation, 10 and ion exchange, 11 have been developed to remediate Cr(VI) contamination. Among them, physicochemical adsorption is an efficient way to remove Cr(VI).…”
Section: Introductionmentioning
confidence: 99%